Lower and upper bounds of the Čebyšev functional for the Riemann-Stieltjes integral - Dragomir, S.S.; Sofo, A. (Italian Journal of Pure and Applied Mathematics, 2011)
Lower and upper bounds of the Čebyšev functional for the Riemann-Stieltjes integral, in the monotonicity case of one function, are given. Applications in relation with the Steffensen generalisation of the Čebyšev inequality are provided.